Incidence of Emergence Delirium in the Pediatric PACU: Prospective Observational Trial - Eva Klabusayová; Tereza Musilová; Dominik Fabián; Tamara Skříšovská; Václav Vafek; Martina Kosinová; Michaela Ťoukálková; Adéla Vrtková; Jozef Klučka; Petr Štourač (MDPI AG, 2022)
Emergence delirium (ED) is a postoperative complication in pediatric anesthesia characterized by perception and psychomotor disorder and has a negative impact on morbidity in the form of maladaptive behavior, which can last weeks after anesthesia. Patients with developed ED present with psychomotor anxiety, agitation, and are at higher risk of unintentional extraction of an intravenous cannula, self-harm and nausea and vomiting. The described incidence of ED varies between 25-80%, with a higher prevalence among children younger than 6 years of age. We aimed to determine the incidence of ED in pediatric patients (>1 month) after general anesthesia in the post-anesthesia care unit (PACU), using Paediatric Anaesthesia Emergence Delirium (PAED) score, Watcha score and Richmond agitation and sedation scale (RASS). The incidence of ED was the highest in the PAED score with cutoff ≥10 points (89.0%, n = 1088). When using PAED score >12 points, ED incidence was 19.3% (n = 236). The lowest incidence was described by Watcha and RASS scores, 18.8% (n = 230) vs. 18.1% (n = 221), respectively. The threshold for PAED ≥10 points seems to give false-positive results, whereas the threshold >12 points is more accurate. RASS scale, although intended primarily for estimation of the depth of sedation, seems to have a good predictive value for ED.